DNA Sequences of LasB Gene in Pseudomonas aeruginosa Isolated from Some Clinical Cases - M. A. Al-Shwaikh, Rana (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Out of 120 isolates from different clinical cases, only 75 were found and confirmed that they belong to the Pseudomonas aeruginosa bacteria. The result revealed that the LasB virulent gene was present in 63 isolates with 63% percentage. The gel electrophoresis showed that the molecular weight of LasB gene was 300 bp. DNA sequences of LasB gene was done, and the results showed the presence of some gene mutations like substitution, addition and deletion with 97% identity with the Refseq gene. From the other side, the results of identities of translated nucleotides sequence with the original sequence of amino acids revealed that there are no effects of gene mutations on translation of the product protein.